Effect of manipulated environmental condition on the distribution of Aero-algal Counts - Pandkar, Jogita. T. (Current Botany)
Reports on occurrence, distribution pattern, listing of aero-algal forms, seasonal calendar, allergenic aero-algal forms, effect of meteorological parameters on occurrence of aero-algal forms etc. has been reported by number of aerophycologists. But solution on reducing such aero-algal counts which can be a possible cause for allergenic reaction has not been suggested until known. Hence preliminary study with respect to effect of manipulated environmental condition on the distribution of aero-algal counts has been done. Presence of cooling tower results into manipulation of the climatic factors, such as temperature and humidity percentage. The high humidity percentage act as an unfavorable condition for the surviving of aero-algal forms resulting into sporulation. This spores required some incubation period under favourable condition to undergo for its vegetative development. This knowledge can be used as a possible solution for the allergenic patients. Manipulation of climatic factors can be done both at intramural as well as extramural sites by using water coolers, A.C, introducing water falls etc. It can be considered as possible manageable solution for patient suffering from allergy due to aero-biological pollutants.